Implementation Of Human Oriented Head Supervision In MIN 3 Balangan Halong District - Hj. Norlaila Hj. Norlaila (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
As the head of the madrasa, of course, he is faced with several complex problems, especially in understanding the administration of madrasa management, therefore the head of the madrasa is required to have basic skills in supervising in matters of religion, professionalism, managerial and competition. This study aims to explain the implementation of madrasa head supervision on a human-oriented basis at MIN 3 Balangan Halong District. The research method used is a qualitative method with the type of research narrative research and data collection by means of observation and interviews. The data obtained is then reduced, data display and data verification. The results of the study explain that the principal at MIN 3 Balangan Halong District uses a human-oriented approach in the implementation of their supervision, including by personal approach to teachers who experience problems in learning, two-way discussions in the principal's office, guidance on problems faced by teachers by means of peer tutoring. and improving the quality of teachers by providing trainings in collaboration with external parties who have the competence to solve teacher problems. This research contributes to the supervision pattern of madrasah principals in a more elegant and humane way for teachers without dropping and degrading the professionalism of the guidance teachers. two-way discussions in the principal's office, guidance on problems faced by teachers by conducting peer tutoring and improving the quality of teachers by providing trainings in collaboration with external parties who have the competence to solve teacher problems. This research contributes to the supervision pattern of madrasah principals in a more elegant and humane way for teachers without dropping and degrading the professionalism of the guidance teachers. two-way discussions in the principal's office, guidance on problems faced by teachers by conducting peer tutoring and improving the quality of teachers by providing trainings in collaboration with external parties who have the competence to solve teacher problems. This research contributes to the supervision pattern of madrasah principals in a more elegant and humane way for teachers without dropping and degrading the professionalism of the guidance teachers.